Manipulating liquids with robots: A sloshing-free solution. (September 2018) - Moriello, Lorenzo; Biagiotti, Luigi; Melchiorri, Claudio; Paoli, Andrea
Abstract: This paper addresses the problem of suppressing sloshing dynamics in liquid handling robotic systems by an appropriate design of position/orientation trajectories. Specifically, a dynamic system, i.e. the exponential filter, is used to filter the desired trajectory for the liquid-filled vessel moved by the robot and counteract the sloshing effect. To this aim, the vessel has been modelled as a spherical pendulum of proper mass/length subject to the accelerations imposed by the robot and the problem has been approached in terms of vibration suppression to cancel the residual oscillations of the pendulum, i.e. the pendulum swing at the end of the reference rest-to-rest motion. In addition, in order to reduce the relative motion between liquid and vessel, an orientation compensation mechanism has been devised aiming to maintain the vessel aligned with the pendulum during the motion. The effectiveness of the proposed approach, both in simple point-to-point motions and complex multi-point trajectories, has been proved by means of an exhaustive set of experimental tests on an industrial manipulator that moves a cylindrical vessel filled with water. This innovative solution effectively uses all the degrees of freedom of the robotic manipulator to successfully suppress sloshing, thus significantly improving the performances of the robotic system. Furthermore, the proposed solution, showing a high degree of robustness as well as intrinsic design simplicity, is very promising for designing novel industrial robotics applications with a short time-to-market across key manufacturing sectors (e.g., food and beverage, among others).